2017
DOI: 10.1128/jvi.01858-16
|View full text |Cite
|
Sign up to set email alerts
|

Ribosome Profiling Reveals Translational Upregulation of Cellular Oxidative Phosphorylation mRNAs during Vaccinia Virus-Induced Host Shutoff

Abstract: Vaccinia virus infection causes a host shutoff that is marked by global inhibition of host protein synthesis. Though the host shutoff may facilitate reallocation of cellular resources for viral replication and evasion of host antiviral immune responses, it poses a challenge for continuous synthesis of cellular proteins that are important for viral replication. It is, however, unclear whether and how certain cellular proteins may be selectively synthesized during the vaccinia virus-induced host shutoff. Using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
49
2

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 73 publications
(96 reference statements)
4
49
2
Order By: Relevance
“…Analysis of cellular mRNAs less-sensitive to this global shut-down of translation identifies several host proteins that promote viral replication. Similar analyses revealed the abundance of viral mRNA contributes to the host-cell shut-off for other viruses including coronaviruses, influenza and vaccinia [47][48][49].…”
mentioning
confidence: 74%
“…Analysis of cellular mRNAs less-sensitive to this global shut-down of translation identifies several host proteins that promote viral replication. Similar analyses revealed the abundance of viral mRNA contributes to the host-cell shut-off for other viruses including coronaviruses, influenza and vaccinia [47][48][49].…”
mentioning
confidence: 74%
“…Two recent studies, one from our group and one from Stern-Ginossar's group, respectively, employed simultaneous RNA-Seq and Ribo-Seq to provide systematic views of VACV-and IAV-induced host shutoff (8,24). The studies found that, during both viral infections, host shutoff is driven by mRNA depletion (likely triggered by virus-encoded proteins that rapidly degrade host cell mRNAs).…”
Section: Oxidative Phosphorylation Proteins As Targets For Selective mentioning
confidence: 99%
“…When oxidative phosphorylation is impaired by chemical compounds in VACV-or IAV-infected cells, viral replication is significantly reduced (8,24), demonstrating that oxidative phosphorylation is important in their life cycles. In addition to providing energy for viral replication, increasing or maintaining ATP levels may also prevent viral protein aggregation due to large amount of viral protein production during replication (26).…”
Section: Oxidative Phosphorylation Proteins As Targets For Selective mentioning
confidence: 99%
See 2 more Smart Citations